Medial tibial stress syndrome: conservative treatment options - Galbraith, R. Michael (Humana Press Inc, 2009)
Medial tibial stress syndrome (MTSS), commonly known as “shin splints,” is a frequent injury of the lower extremity and one of the most common causes of exertional leg pain in athletes (Willems T, Med Sci Sports Exerc 39(2):330–339, 2007; Korkola M, Amendola A, Phys Sportsmed 29(6):35–50, 2001; Hreljac A, Med Sci Sports Exerc 36(5):845–849, 2004). Although often not serious, it can be quite disabling and progress to more serious complications if not treated properly. Often, the cause of MTSS is multi-factorial and involves training errors and various biomechanical abnormalities. Few advances have been made in the treatment of MTSS over the last few decades. Current treatment options are mostly based on expert opinion and clinical experience. The purpose of this article is to review published literature regarding conservative treatment options for MTSS and provide recommendations for sports medicine clinicians for improved treatment and patient outcomes.